AN INVESTIGATION OF TEACHERS' TEACHING STRATEGIES IN ACCOMMODATING EFL STUDENTS VOCABULARY LEARNING:CASE STUDY AT A SENIOR HIGH SCHOOL IN GARUT - Panji, Aceng Mahmud (2012)
This thesis reported on the issues of teaching, particularly the teaching of EFL vocabulary to senior high school students in Indonesia. It sought to explore the strategies used by four English teachers in teaching EFL vocabulary in accommodating the learners' learning strategies, some problems faced by the teachers, and the ways of solving such problems. This research employed a qualitative case study research design. The data were obtained from various sources, including questionnaires, classroom observation, and an interview conducted to all teachers soon after the program. All these instruments were use to triangulate the results of analysis done afterwards. The results showed that the teachers to some extent have been able to demonstrate appropriate vocabulary teaching strategies to accommodate the learners' vocabulary learning strategies as outlined in learners' taxonomy of vocabulary learning strategies. The teachers had successfully attempted to use some of the main conventions of vocabulary teaching strategies such as Determination Strategy, Social Strategy, Memory Strategy, Cognitive and Metacognitive Strategies. Those strategies have been presented within a series of teaching techniques such as making use of various teaching media, engaging students in collaborative learning through class, group and pair work, providing direct translation, learning through some games, working on various exercises, drilling on pronunciation and spelling of words, etc. However, despite the findings above, the discussions also reveal that not all of the teachers can successfully implement some other necessary strategies in the classroom processes which may also be helpful to support students' learning.